Adult BMI Change and Risk of Colon Cancer in Postmenopausal Women - Lyla Blake-Gumbs; Zhengyi Chen; Cheryl L. Thompson; Nathan A. Berger; Thomas C. Tucker; Li Li (Journal of Obesity)
Purpose. We recently reported an association of adult BMI change with colon cancer risk. Here, we sought to further explore this association with respect to postmenopausal HRT use in a larger study population. Methods. We included 1,457 postmenopausal women participating in an ongoing population-based case-control study of colon cancer. Results. We confirmed a previously reported association of adulthood weight gain and increased risk of colon cancer: compared to those with <5 kg/m2 change of BMI, women who reported moderate (5–10 kg/m2) and large (>10 kg/m2) BMI changes since their 20s had OR estimates of 1.54 (95% CI = 1.09–2.19) and 1.45 (95% CI = 0.90–2.33), respectively (P for trend = 0.05). Stratified analyses showed that this association was limited to HRT nonusers: ORs were 1.77 (95% CI = 1.02–3.05) and 2.21 (95% CI = 1.09–4.45), respectively (P for trend = 0.03), for BMI changes occurring between the 20s decade and time of recruitment among non-users. Similar associations were observed for BMI changes since the 30s decade. There was no association among HRT users. Conclusion. Our results suggest early adulthood weight gain increases colon cancer risk in postmenopausal women who do not use HRT.